A revision of the New World species of the Aleiodes compressor species group (Hymenoptera: Braconidae: Rogadinae). Issue 6 (16th March 2015) - Shimbori, Eduardo M.; Shaw, Scott R.; Penteado-Dias, Angélica M.
Abstract: Species of the Aleiodes compressor (Herrich-Schaeffer) species group (Hymenoptera: Braconidae: Rogadinae) from the New World are revised. Two new species are described ( Aleiodes mantiqueirensis new species and Aleiodes marinonii new species ) and geographical range of the species group is extended into the Neotropical Region. Both new species are known only from the type locality in Brazil. Including the current descriptions, there are six species within the Aleiodes compressor species group, four of them from the New World. Some new diagnostic characters for the group are proposed such as the relative length of antenna and the shape of ovipositor sheaths. The males of this group are difficult to distinguish from males of the Aleiodes gastritor-circumscriptus species group because most diagnostic features are found only in females.